SCAFFOLDING IN THE TEACHING OF WRITING DISCUSSION TEXTS BASED ON SFL - GENRE BASED APPROACH - Syarifah, Eva Fitriani (2016)
This study focuses on the issue of scaffoldings in the teaching of writing discussion texts based on SFL - Genre Based Approach. It particularly aims to investigate how scaffolding processes are implemented in the teaching of writing discussion texts based on SFL-GBA and how they improve the students' writing performance. The data rely on teaching and learning process in a classroom with six students in a tertiary level as the focus participants. The method used in the data analysis adopted a qualitative design with reference especially to the theory of scaffolding and SFL-GBA. The results of analysis show that scaffolding processes are implemented in terms of macro and micro scaffoldings and able to improve the students' writing performance specifically in terms of social function, schematic structure, and language features of discussion genre. It is recommended that future related research should be conducted in more diverse educational settings to see how scaffoldings are implemented. Keywords: scaffolding, discussion texts, SFL - Genre Based Approach. Penelitian ini mengacu pada isu scaffolding dalam pengajaran menulis teks diskusi berdasarkan pendekatan SFL - Genre Based. Penelitian ini bertujuan untuk mencari tahu bagaimana proses scaffolding diimplementasikan dalam pengajaran menulis teks diskusi berdasarkan pendekatan SFL-Genre Based dan bagaimana scaffoding tersebut bisa meningkatkan kemampuan menulis siswa. Data penelitian ini diperoleh dari kegiatan pembelajaran di dalam dan enam siswa pada level universitas sebagai fokus penelitian ini. Metode yang digunakan dalam data analysis mengacu pada desain kualitatif berdasarkan teori scaffolding dan SFL-GBA. Hasil analisis menunjukan bahwa proses scaffolding diimplementasikan dalam cakupan makro dan mikro scaffolding dan mampu meningkatkan kemampuan menulis siswa terutama dalam segi tujuan penulisan teks, struktur teks, dan tata bahasa yang digunakan dalam teks. Disarankan kepada peneliti yang akan melakukan penelitian serupa untuk melakukan penelitian dalam cakupan yang berbeda. Kata Kunci: scaffolding, teks diskusi, pendekatan SFL - Genre Based.